2000
DOI: 10.1128/.68.11.6441-6448.2000
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Peptidoglycan-Associated Lipoprotein Is Required for Virulence in the Human Model of Haemophilus ducreyi Infection

Abstract: Haemophilus ducreyi expresses a peptidoglycan-associated lipoprotein (PAL) that exhibits extensive homology to Haemophilus influenzae protein 6. We constructed an isogenic PAL mutant (35000HP-SMS4) by the use of a suicide vector that contains lacZ as a counterselectable marker. H. ducreyi 35000HP-SMS4 and its parent, 35000HP, had similar growth rates in broth and similar lipooligosaccharide profiles. 35000HP-SMS4 formed smaller, more transparent colonies than 35000HP and, unlike its parent, was hypersensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…BMA2082) was present in very low abundance and only in some of the conditions tested [54]. A review of the literature indicated that Pal is produced at readily detectable levels by most organisms in which expression of the protein has been studied including E. coli [55], Haemophilus influenzae [56], Erwinia chrysanthemi [57], Pseudomonas aeruginosa [58], and Haemophilus ducreyi [59]. Hence, the pal gene appears to be more stringently regulated in B. mallei.…”
Section: Discussionmentioning
confidence: 99%
“…BMA2082) was present in very low abundance and only in some of the conditions tested [54]. A review of the literature indicated that Pal is produced at readily detectable levels by most organisms in which expression of the protein has been studied including E. coli [55], Haemophilus influenzae [56], Erwinia chrysanthemi [57], Pseudomonas aeruginosa [58], and Haemophilus ducreyi [59]. Hence, the pal gene appears to be more stringently regulated in B. mallei.…”
Section: Discussionmentioning
confidence: 99%
“…Comparisons of the phenotypic characteristics of the mutant and parent may, however, provide preliminary information about the role and function of AaPAL in A. actinomycetemcomitans cell physiology. We found that the mutants had decreased growth rate and filamentous cell morphology, differing partly from the pal -deficient mutant of H. ducreyi , which showed unchanged growth rate [ 14 ]. Although there were limitations in the present methods for estimating bacterial numbers, our results are consistent with previous reports demonstrating reduced growth rate of bacteria with mutations in tol-pal genes [ 13 , 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proinflammatory and prochemotactic properties of AaPAL may contribute to producing a long-term immune challenge in persistent A. actinomycetemcomitans -associated infections. The extracellular release of PAL is also of more general interest because bacterial lipoproteins are increasingly being recognized as playing an important role in bacterial pathogenicity [ 7 , 14 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out on healthy individuals showed that in comparison with the wild-type strain, an H. ducreyi pal mutant caused less profound skin changes that rarely transformed into ulcerating forms and fewer bacteria were isolated from biopsy samples taken from the forming wound. This finding could be due to the decreased survival of pal mutants or a reduced ability to induce an immune response and the lower numbers of neutrophils, lymphocytes, macrophages or dendritic cells recruited to the site of infection (Fortney et al, 2000).…”
Section: Haemophilus Ducreyimentioning
confidence: 99%